Analisis Perancangan Video Promosi Koran Digital Batam Pos: Case Study Menggunakan Metode Design Thinking - Amadia, Rini; Nurani H, Tia Cahya (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
In terms of news delivery, especially after the Covid-19 pandemic, the transition from print media to digital media has accelerated, just as Batam Pos must be prepared to face various challenges in the digital realm. One solution implemented by Batam Pos is to shift the medium of news delivery from a print newspaper to a digital newspaper. Although it has been running since the end of 2023, many people are still unaware that the Batam Pos print newspaper can be accessed digitally. As of January 2025, the total number of digital newspaper subscribers for Batam Pos is only 60, with a target of 2500 subscribers to be achieved by the end of 2025. Therefore, this research was conducted to promote the Batam Pos digital newspaper to the public using the design thinking method. This research uses a quantitative approach with validation testing by the content production manager of Batam Pos, followed by testing using the Single Ease Question (SEQ) method on 100 respondents. The evaluation results show an SEQ score of 4.06, which falls into the good/successful category. This research concludes that the designed promotional video is able to meet the information needs of potential customers regarding the subscription process and benefits and has the potential to increase the number of Batam Pos digital newspaper subscribers.